User and Healthcare Professional Perspectives on Do-It-Yourself Artificial Pancreas Systems: A Need for Guidelines. (January 2022) - Shepard, Jaclyn A.; Breton, Marc; Nimri, Revital; Roberts, Joseph T. F.; Street, Timothy; Klonoff, David; Barnard-Kelly, Katharine
A growing number of individuals with type 1 diabetes are choosing to use "do-it-yourself" artificial pancreas systems (DIY APS) to support their diabetes self-management. Observational and self-report data of glycemic benefits of DIY APS are promising; however, without rigorous clinical trials or regulation from governing bodies, liability and user safety continue to be central concerns for stakeholders. Despite DIY APS having been used for several years now, there are no guidelines to assist users and healthcare professionals in addressing DIY APS use in routine clinical care. This commentary reports key stakeholders' perspectives presented at the annual Advanced Technologies and Treatments in Diabetes conference in February 2020. Important considerations to inform the development of clinical care guidelines are also presented to generate further debate.